(untitled) (Bangladesh Journal of Medical Science, 2021)
Objective: The aim of this study was to examine the bacterial growth of the attendants’ hands and to determine the difference between the hospitalized and non-hospitalized attendants’ hands’ bacterial growth. Materials and Methods: In this study, the samples taken from the hands of attendants who were accompanying the hospitalized patients were examined. As a control group attendants who were not hospitalized was chosen. The samples were taken from the attendants’ hands and between the fingers using the swap which was wetted by steril serum physiological. Samples were inoculated to bood agar (BA) and eosine methylene blue agar (EMB) immediately. Inoculated plates were incubated 24-48 hours at 370C and growth was evaluated. Growth was identified using colony morphology, Gram stain, catalase and oxidase reaction. Catalaz positive bacteria were investigated for beta hemolysis, colony morphology on BA, Gram stain and microscopic appearance. Growth characteristics of Gram-negative bacilli on EMB and microscopic appearance were determined. All samples were identified by Vitec II. Results: All participants were women and their average age were 28.93±6.09 (min=18, max=45). It was determined that the rate of bacterial growth was 10% in case group and there was not growth in control group. The difference was statistically insignificant (χ² = 5.263, p = 0.056). Conclusions: In conclusion, the bacterial growth on 10% of participants’ hands in case group is an important and remarkable result. Being at the border of statistical difference between the two groups suggest that similar studies should be conducted with a larger sample group. Bangladesh Journal of Medical Science Vol.20(2) 2021 p.263-267